Efficiency Estimation of Constructing of Wind Power Plant for the Heat Supply Needs - A. V. Bezhan (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
As in the whole world, there are regions in Russia that experience heat supply difficulties, mainly due to the high cost of fossil fuel as well as to growth of energy resources cost and polluting emissions. In this regard, search for solutions which would provide energy saving with an increase of energy, commercial and ecological efficiency of modern heat supply systems is becoming vitally important today. One of them is the development and use of special types of energy including renewable energy sources, wind energy in particular. Accordingly, the paper presents one of the possible solutions to the heat supply problem which are directed at meeting the whole region’s heat demand through the joint use of wind power plants with a boiler room operating on fuel oil. The study assessed the efficiency of constructing of wind power plants with a total capacity of 1.7 MW for the heat supply needs of a settlement, which is located on the Barents Sea coast in Russia. The selected area is characterized by an average annual wind speed of 7.0 m/s and a long heating period (9–10 months a year). The assessment showed that the wind power plant construction is financially reasonable, as additional profit can be generated by the end of the wind power plants scheduled service life that make up the half of primary investments. The results obtained in the paper are expected to make up for the lack of information on the feasibility of wind power plants construction for the heat supply needs, which is very useful for other countries that have similar areas experiencing various heat supply difficulties.